541 participated in Sarawak Invention, Innovation & Design Exposition (SIIDEx) 2019 - Idris, Juferi; Tambi, Hanita; Ku Azir, Ku Mohammad Asyraf; Morni, Fareiny; Chan, Geraldine (UiTM Sarawak, 2020)
The Innovation and Design Expo 2019 (SIIDEx 2019) held at the CIDB Convention Centre Kuching on 21st - 23rd October 2019 was a collaboration between UiTM Sarawak, Sarawak Education Department (JPNS) and Sarawak Multimedia Authority (SMA). SIIDEx was created as a natural platform to promote and nurture interest in Science and Technology amongst school students in Sarawak.